2000
DOI: 10.1007/s004060070016
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality in bipolar compared to unipolar depressed inpatients

Abstract: The aim of the present analyses was to evaluate differences in suicidality (past suicide attempts, suicidal thoughts at time of admission and completed suicides during the hospital stay) between bipolar and unipolar depressed inpatients. Apart from a higher frequency of past suicide attempts in bipolar depressed patients (26.6% in bipolar vs. 17.8% in unipolar patients), findings do not indicate any further differences in suicidality (suicidal thoughts (about 40% in both groups) and completed suicides during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 0 publications
4
31
0
3
Order By: Relevance
“…Although some studies found a somewhat lower suicide rate in bipolar as compared to unipolar patients [15,16] , others found higher rates in bipolar patients [17][18][19] , particularly in bipolar II patients.…”
Section: Suicide Risk and Mortality Of Patients With Affective Disordersmentioning
confidence: 96%
“…Although some studies found a somewhat lower suicide rate in bipolar as compared to unipolar patients [15,16] , others found higher rates in bipolar patients [17][18][19] , particularly in bipolar II patients.…”
Section: Suicide Risk and Mortality Of Patients With Affective Disordersmentioning
confidence: 96%
“…Rates of the disorder decline as income and education levels increase [3]. Individuals with bipolar disorder face an increased risk of developing alcoholism [4•], and of dying from suicide [5]; moreover, their risk of suicide increases substantially when bipolar disease is comorbid with alcoholism [6]. Both lithium carbonate and anticonvulsive agents are commonly prescribed for the disorder's treatment, and they are effective in treating both the depressive and manic phases of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Reports of the prevalence of suicidal ideation vary from 14% to 59% in bipolar samples [20][21][22][23][24][25] and only a few cross-sectional studies have examined variables that influence suicidal ideation in BD and its relationship with suicide attempts. Some risk factors associated with the presence of suicidal ideation are positive family history for affective disorder, severe depression, 12 psychotic symptoms, 26 past suicide attempt, 23,26 comorbidity with alcohol abuse or dependence, 23 panic spectrum symptoms, 27 and earlier age of onset. 28 Valtonen et al, in a cross-sectional study with a sample of 191 patients with bipolar disorder, showed that 61% (n = 116) reported suicidal ideation during the index-episode and 20% (n = 39) had attempted suicide in the same episode.…”
Section: Stress-diathesis Modelmentioning
confidence: 99%